Information Hiding using Steganography and LSB Technique - Asheesh Tiwari, Piyush Vashistha, Ajeet Kumar Sharma (International Journal of Advanced Science and Technology, 2020)
Steganography is a practice of embedding a file into another file in such a way that other people cannot recognize or even know the significance of the hidden document. Recent research patterns use a digital image to hide another digital image consisting of a sensitive message or information as the cover file. Steganography becomes more relevant as more people participate in the revolution of cyberspace. Steganography is an art of hiding the information in such a manner that hidden messages are prevented from being detected. The purpose of Steganography is to avoid drawing impression into the presence of a hidden message. Recently this hiding information approach has become relevant in a number of different areas of application. We proposed a new methodology for using cryptographic Steganographic technique to provide security features to the secret message that senders and users have to share with each other. Military communications networks use traffic protection methods that aim to mask its sender, its recipient or its very nature, rather than simply hiding the message content by using encryption technique. Any mobile phone applications and schemes suggested for digital elections employ similar types of techniques. One of the most common implementation methods is LSB in which we modify the LSB of each byte to form the byte-string that represents the embedded file.Keywords:  Steganography, Encryption, LSB Insertion, etc.